2014
DOI: 10.1122/1.4882955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weak attractive interactions on flow behavior of highly concentrated crystalline suspensions

Abstract: SynopsisWeak attractive interactions lead to a substantial broadening of the fluid-crystalline coexistence region of crystalline, colloidal hard-sphere dispersions. Here, we demonstrate that a weak depletion attraction introduced by nonadsorbing polymer added to the continuous phase results in a strong decrease of the low shear viscosity even at particle concentrations up to U ¼ 0.65 analogous to the re-entry phenomenon in highly concentrated glassy systems. This promotes flow in macroscopic channels but the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…A substantial reduction in viscosity was observed for ϕ polymer = 3 g/l whereas η drastically increased at ϕ polymer = 10 g/l compared to the pure suspension. Similar results with a pronounced minimum in low shear viscosity as a function of polymer concentration were found for other particle loadings and were also reported previously for a similar colloidal suspension, but at different ϕ, ϕ polymer , and M w 43 .…”
Section: Resultssupporting
confidence: 91%
“…A substantial reduction in viscosity was observed for ϕ polymer = 3 g/l whereas η drastically increased at ϕ polymer = 10 g/l compared to the pure suspension. Similar results with a pronounced minimum in low shear viscosity as a function of polymer concentration were found for other particle loadings and were also reported previously for a similar colloidal suspension, but at different ϕ, ϕ polymer , and M w 43 .…”
Section: Resultssupporting
confidence: 91%
“…Recent studies have found that for dense suspensions stabilized by short range repulsion (as it is the case for Curosurf® vesicles), the addition of weak attractive interaction leads to a decrease in viscosity. [59][60][61][62] In these reports, the colloids are beads and microgels and the attraction is due to depleting non-adsorbing polymers. 59,61,62 It was found that a minute amount of depleting agents leads to the formation of large cohesive aggregates and thereby to a decrease of the effective volume fraction.…”
Section: Ii3 -Alumina Loaded Surfactant Showing a Soft Solid Behaviormentioning
confidence: 99%
“…[59][60][61][62] In these reports, the colloids are beads and microgels and the attraction is due to depleting non-adsorbing polymers. 59,61,62 It was found that a minute amount of depleting agents leads to the formation of large cohesive aggregates and thereby to a decrease of the effective volume fraction. As a result, the suspension bulk viscosity decreases, in proportions similar to those of Fig.…”
Section: Ii3 -Alumina Loaded Surfactant Showing a Soft Solid Behaviormentioning
confidence: 99%
“…A number of recent studies have used the above mentioned adaptations and gap error corrections of parallel-plate setups with micrometer gap separations with a focus on studying fluids a high shear rates [23,24,46,60,75], and on confinement effects [23,24,46,89,95]. In addition, these setups have been used to study small sample volumes [60], and to mimic usage or processing environment conditions [23,46,89].…”
Section: Adaptations To a Conventional Rotational Rheometermentioning
confidence: 99%